Experimental and numerical analyses of a deep foundation containing a single defective pile - Freitas Neto, Osvaldo de (2020)
The methodologies for designing pile foundations can be complex since the simultaneous interactions among the block, piles and surrounding soil should be taken into account. Therefore, in addition to the discussions on construction, instrumentation, testing and simulation of a defective pile, this paper discusses the practical issues arising from the observed numerical using three-dimensional finite elements and experimental studies. The main issues discussed in this paper refer to as the decrease in load capacity of bored instrumented piles when subjected to a structural defect. It was observed in the results that given the presence of the defect, the failure load of the system has decreased from 190 kN to 110 kN, i.e. around 40% reduction of the intact reference value. Using the data obtained by numerical analysis, laboratory test, and field application, it was possible that the results were satisfactory and reasonable, enhancing our understanding of this complex foundation system’s behavior, especially in the presence of a defective pile